Versions of virginity : an exploration of university students' narrative accounts of first sexual experience - Ebden, Tiffany (Rhodes University, Faculty of Humanities, Department of Psychology)
The research assumes a narrative constructionist and feminist perspective in order to explore stories concerning men and women's first sexual experience. Such a metatheoretical stance is concerned with the ways that lives are constructed and storied through language. There is a concern for the myriad voices, both personal and social, that speaks through individuals' stories and for the manner in which these voices are represented. Three men and three women were interviewed to elicit narratives of first sexual experience. The analysis of interview transcripts tells first sexual experience as a rite of passage described in terms of certain mythic elements. That is, the experience of first sex concerns three stages. Firstly the individual is detached from the experience of sex while still a virgin. Secondly the experience itself is one that is ineffable and diffuse. Thirdly the individual must make sense of the experience. Participants' experience could be characterised as containing elements of demonic, heavenly or earthly myths about sexual relationships: demonic elements concerned the base , physical and painful experiences of first sex; the myth of heavenly love emphasises the mental and emotional connection between partners; an earthly myth tells sex as a predestined meeting of two partners. The manner in which stories were constructed was different for male and for female participants, and these differences have implications for the power dynamics at play between genders in the context of sexual interaction, especially first sex. Further the research's storied and ritualised approach to these gender differences suggests the performative aspect of gender.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: College students -- South Africa -- Sexual behavior; Sexual intercourse -- Psychological aspects; Virginity